2014
DOI: 10.1007/s12031-014-0476-3
|View full text |Cite
|
Sign up to set email alerts
|

Selected Extracellular microRNA as Potential Biomarkers of Multiple Sclerosis Activity—Preliminary Study

Abstract: Multiple sclerosis (MS) is an autoimmune demyelinating disease of the central nervous system (CNS). Four distinct disease courses are known, although approximately 90 % of patients are diagnosed with the relapsing-remitting form (RRMS). The name “multiple sclerosis” pertains to the underlying pathology: the presence of demyelinating plaques in the CNS, in particular in the periventricular region, corpus callosum, cervical spine, and the cerebellum. There are ongoing efforts to discover biomarkers that would al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…In our recent work, we identified concurrent downregulation of 4 miRNAs (miR-126-3p, miR-145-5p, miR-199a-5p, and miR-223-3p) in both CD4 + and CD8 + T cells from AA patients, 14 but dysregulation of the 4 miRNAs was not observed in AA plasma samples in the study herein. Previous reports in autoimmune diseases 12,20,[52][53][54][55][56][57][58][59] and cancers, [60][61][62][63] have also demonstrated discrepancies of expression profiles between cellular and circulating miRNAs. Systemic lupus erythematosus (SLE) patients exhibit distinct miRNA expression profiles in T cells [52][53][54][55] and plasma, 56 and miRNA profiles in T cells 12,57,58 and plasma 20,59 are inconsistent in MS.…”
Section: Discussionmentioning
confidence: 91%
“…In our recent work, we identified concurrent downregulation of 4 miRNAs (miR-126-3p, miR-145-5p, miR-199a-5p, and miR-223-3p) in both CD4 + and CD8 + T cells from AA patients, 14 but dysregulation of the 4 miRNAs was not observed in AA plasma samples in the study herein. Previous reports in autoimmune diseases 12,20,[52][53][54][55][56][57][58][59] and cancers, [60][61][62][63] have also demonstrated discrepancies of expression profiles between cellular and circulating miRNAs. Systemic lupus erythematosus (SLE) patients exhibit distinct miRNA expression profiles in T cells [52][53][54][55] and plasma, 56 and miRNA profiles in T cells 12,57,58 and plasma 20,59 are inconsistent in MS.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, its blood concentration should correlate with its content in the cerebrospinal fluid (CSF) [13]. Such a marker should appear in various bodily fluids shortly after the onset of the disease, and should react in response to treatment in order to be used as a prognostic tool.…”
Section: The Stability Of Plasma Mirna and Their Use As Biomarkersmentioning
confidence: 99%
“…Current knowledge of the biological functions of extracellular miRNA is still very limited. Early studies have indicated that cellular miRNA and extracellular miRNA found in plasma could be negatively correlated [13,19,30]. MicroR-NA seem to be universal prognostic factors.…”
Section: Selection Of Mirna As Precise Biomarkers Of Multiple Sclerosismentioning
confidence: 99%
“…Intriguingly, while RNA molecules in the cell tend to be short-lived, circulating microRNAs show much higher stability and are protected from degradation by endogenous RNases [14]. Altered levels of specific microRNAs in body fluids have been linked to a wide range of diseases, including disorders of the nervous system [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Serum microRNA levels were altered in children with autism spectrum disorders and salivary levels have been correlated with neurodevelopmental scores [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…disease [17][18][19][20], Parkinson's disease [16,21], Huntington's disease [22] and multiple sclerosis [23,24], as well as glioma [25][26][27] and stroke [28]. MicroRNA levels in the CSF were used to differentiate between glioblastoma and brain metastatic cancers [27].…”
Section: Introductionmentioning
confidence: 99%